Efficiency of Endovascular Haemostasis at Delivery in Patients with Previa and Placenta Invasion - T. B. Makukhina; V. A. Khorolsky; S. P. Nikitin; A. Yu. Bukhtoyarov; A. V. Solntseva; M. A. Tabelova; A. S. Sumaneeva (Кубанский научный медицинский вестник, 2020)
Aim. Analysis of operative delivery outcomes in pregnant women with abnormal invasive placenta depending on the endovascular treatment for intraoperative haemostasis.Materials and methods. A retrospective study of operative delivery outcomes was performed in 178 patients with placental invasion using ultrasonography (US) data obtained at the Perinatal Centre of the Regional Clinic Hospital No. 2, Ministry of Health of Krasnodar Krai, in the years 2012–2018. In 2012–2014, delivery was managed without endovascular haemostasis (n = 44), and from May 2014 to December 2018 – with prophylactic balloon catheterization of common iliac arteries (n = 134). Upon intraoperative diagnosis of placental invasion, temporary balloon occlusion (TBO, n = 115) and/or uterine artery embolization (UAE, n = 33) were performed. Efficiency of endovascular methods for intraoperative haemostasis was assessed by comparing the degree of placental invasion, amount of blood loss and transfusion, frequency of hysterectomies (HE), duration of surgery, length of stay in intensive care units (ICU) and outcomes for the foetus.Results. Adoption of endovascular methods for intraoperative haemostasis allowed the blood loss (p = 0.02), haemotransfusion (p = 0.012) and HE frequency (p <0.001) to be significantly reduced. In the absence of clinical and histological manifestations of placental invasion, no difference in blood loss was detected between the groups. The amount of blood loss increased with the degree of invasion. Surgery duration in patients with TBO was signifi cantly longer (p = 0.04). No difference was detected between the groups with respect to the ICU length of stay and outcomes for the foetus.Conclusions. Establishment of endovascular haemostasis at the planned delivery of pregnant women with abnormal invasive placenta allows the blood loss and HE frequency to be reduced. Further improvement of US diagnostics of placental invasions is essential in pre-selection of patients for X-ray surgical care.